Pelatihan Penggunaan Content Management System dengan Wordpress untuk Website Umum dan Bisnis pada Siswa SMK Negeri 1 Sorong - Joe Yuan Mambu; Green Sandag; Erienika Lompoliu; Green Mandias; Marchel Tombeng (Pusat Riset dan Inovasi Nasional, 2022)
Website is one of the main components of the Internet, therefore those who are able to create website may able to influence, share, sell, advertise their or their company/organization content or products. Especially during the Covid-19 era everything information or business has become available online. This community service aimed to teach and bring awareness of CMS, a non coding method and system that can help user to create website quite fast. One of the advantages of WordPress is that it can be used for various websites and applications. For example, you can use WordPress to create a simple website, to a business website. For business websites, one of the plugin modules provided by WordPress is Woocommerce. With Woocommerce users can make WordPress display into an online store or online store quite easily. According to the questionnaire the training gave user a new perspective that creating and publishing website is isn’t that complicated after all when using Wordpress.